Road base composite material as well as preparation method and application thereof

By using lithium slag in the road base composite material and performing secondary hydration reaction with cement, the hydration product is generated to seal harmful substances, which solves the problem of difficult to use lithium slag safely, and achieves low-carbon and safe lithium slag curing and improves the mechanical properties of road base materials.

CN119551949APending Publication Date: 2025-03-04江西宜春市政交通建设有限公司 +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411758287.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to achieve safe and low-carbon utilization of lithium slag, and the initial and final setting time of lithium slag polymer is relatively short, making it difficult to meet the requirements of road engineering.

Method used

Provide a road base composite material, which uses lithium slag directly, and generates hydration products such as C-S-H gel and ettringite through secondary hydration reaction with cement, blocks harmful substances in the lithium slag and reduces their release.

Benefits of technology

It has achieved safe solidification of lithium slag, reduced carbon emissions and energy consumption, improved the mechanical properties and stability of road base composite materials, and met the needs of road base construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166906530000061
    Figure BDA0005166906530000061
  • Figure BDA0005166906530000071
    Figure BDA0005166906530000071
Patent Text Reader

Abstract

The invention belongs to the technical field of road engineering materials, and provides a road base composite material as well as a preparation method and application thereof. The preparation materials of the road base composite material comprise aggregate, cement and water, wherein the aggregate comprises lithium slag, a first aggregate, a second aggregate, a third aggregate and a fourth aggregate. The lithium slag is directly used, mechanical grinding and high-temperature calcination of the lithium slag are avoided, and carbon emission and energy consumption are reduced. And the lithium slag can replace part of the first aggregate and cement, so that the use of the aggregate and cement is reduced, and the cost is reduced. Meanwhile, hydration product calcium hydroxide of cement and active ingredients in the lithium slag are subjected to secondary hydration reaction to form C-S-H gel, ettringite (AFt) and other hydration products, and the hydration products can seal harmful substances and reduce release of the harmful substances; and the hydration product can also increase the compactness of the road base composite material and seal micro-pores of the road base composite material, so that the mechanical property and the shrinkage property of the road base composite material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of road engineering materials, and in particular to a road base composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the lithium battery industry, the amount of lithium slag generated in the lithium salt production process has increased dramatically. However, lithium slag contains toxic substances such as heavy metals. Improper disposal of lithium slag will seriously pollute the environment and endanger the health of humans and animals. In the past, the recycling of lithium slag mainly used mechanical grinding or high-temperature calcination to prepare highly active lithium slag auxiliary gelling materials, or prepared lithium slag geopolymers by alkali activation. In the process of mechanical grinding and high-temperature calcination, not only a large amount of carbon emissions and energy consumption will be generated, but also the cost will be increased, so it is difficult to promote and utilize in actual engineering. The preparation of lithium slag geopolymers by alkali activation will promote the dissolution and recrystallization of aluminosilicates in lithium slag, and the formed lithium slag geopolymers have good gelling properties. However, the use of alkali activators may pose a threat to the health of operators or the ecological environment. Secondly, high-concentration alkali metal solutions will corrode equipment. In addition, the initial and final setting times of lithium slag geopolymers are generally short, which is difficult to meet the requirements of road engineering.

[0003] Therefore, the current application method of lithium slag makes it difficult to achieve safe and low-carbon utilization of lithium slag. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a road base composite material and its preparation method and application. The road base composite material provided by the present invention can solidify harmful substances in lithium slag, thereby realizing the safe application of lithium slag; and the road base composite material directly uses lithium slag without mechanical grinding and high-temperature calcination of lithium slag, thereby reducing carbon emissions and energy consumption; in addition, the obtained road base composite material has excellent mechanical properties and can be used for road base construction.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a road base composite material, comprising the following preparation materials in parts by weight:

[0007] 100 parts of aggregate, 1-5 parts of cement, 4-8 parts of water;

[0008] The aggregate comprises the following components in parts by weight:

[0009] Lithium slag, first aggregate, 15-30 parts of second aggregate, 20-40 parts of third aggregate and 20-30 parts of fourth aggregate;

[0010] The total weight of the lithium slag and the first aggregate is 5 to 35 parts, and the weight of the lithium slag is not 0;

[0011] The particle size of the first aggregate is less than the particle size of the second aggregate, less than the particle size of the third aggregate, and less than the particle size of the fourth aggregate.

[0012] Preferably, the weight of the lithium slag accounts for 1-100% of the total weight of the lithium slag and the first aggregate.

[0013] Preferably, the lithium slag comprises, in terms of weight percentage of oxides: 35-55% SiO2, 15-33% Al2O3, 3-10% K2O, 2-10% Na2O, 3-8% SO3, 0-15% CaO and 0-1.5% Li2O.

[0014] Preferably, the particle size of the lithium slag is less than 2.36 mm.

[0015] Preferably, the first aggregate, the second aggregate, the third aggregate and the fourth aggregate are all made of limestone or limestone.

[0016] Preferably, the particle size of the first aggregate is less than 5 mm, the particle size of the second aggregate is greater than or equal to 5 mm and less than 10 mm, the particle size of the third aggregate is greater than or equal to 10 mm and less than 20 mm, and the particle size of the fourth aggregate is greater than or equal to 20 mm and less than 30 mm.

[0017] Preferably, the cement is PO.42.5 cement.

[0018] The present invention also provides a method for preparing the road base composite material described in the above technical solution, comprising the following steps:

[0019] Mixing aggregate, cement and water to obtain a mixture;

[0020] The mixed material is cured to obtain the road base composite material.

[0021] Preferably, the curing parameters include: ambient humidity of 98% and temperature of 20±2°C.

[0022] The present invention also provides the use of the road base composite material described in the above technical solution or the road base composite material prepared by the preparation method described in the above technical solution in road base construction.

[0023] The invention provides a road base composite material.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) The road base composite material of the present invention directly uses lithium slag, that is, the lithium slag does not need to be mechanically ground or calcined at high temperature, thereby reducing carbon emissions and energy consumption and lowering costs.

[0026] (2) In the road base composite material provided by the present invention, lithium slag is used to replace part of the first aggregate. Since lithium slag contains active ingredients, it can also replace part of the cement. Therefore, the road base composite material provided by the present invention not only fully utilizes the solid waste of lithium slag, but also reduces the use of aggregate and cement, reduces the cost of the road base composite material, and indirectly reduces the carbon emissions of cement and aggregate industrial production.

[0027] (3) The active ingredients in the lithium slag can undergo a secondary hydration reaction with the hydration product Ca(OH)2 of cement to generate hydration products such as CSH gel and calcium aluminate (AFt), which can seal harmful substances and reduce their release. At the same time, the hydration products fill the gaps between the lithium slag particles through physical sealing, reduce porosity and permeability, and prevent the leakage of harmful substances. The high pH environment provided by the hydration products promotes the conversion of many harmful substances into insoluble compounds, further inhibiting the dissolution of harmful substances. In addition, the active ingredients in the lithium slag are converted into stable minerals through secondary hydration reactions, reducing the release of harmful substances. In addition, the hydration products can increase the density of the road base composite material and seal the microscopic pores of the road base composite material, thereby enhancing the mechanical properties and shrinkage properties of the road base composite material. In summary, the road base composite material of the present invention has long-term stability, can continuously enhance the strength of the road base composite material and the ability to seal harmful substances, ensure its long-term control of harmful substances, and realize the safe application of lithium slag.

[0028] (4) The combination of cement, the first aggregate, the second aggregate, the third aggregate, the fourth aggregate and lithium slag of the present invention makes the obtained road base composite material have excellent mechanical properties (including compressive strength, splitting strength, frost resistance and shrinkage performance), so that it can be better applied to road base construction; compared with the lithium slag geopolymer obtained by alkali activation, it has higher application value and is more practical. DETAILED DESCRIPTION

[0029] The present invention provides a road base composite material, comprising the following preparation materials in parts by weight:

[0030] 100 parts of aggregate, 1-5 parts of cement, 4-8 parts of water;

[0031] The aggregate comprises the following components in parts by weight:

[0032] Lithium slag, first aggregate, 15-30 parts of second aggregate, 20-40 parts of third aggregate and 20-30 parts of fourth aggregate;

[0033] The total weight of the lithium slag and the first aggregate is 5 to 35 parts, and the weight of the lithium slag is not 0;

[0034] The particle size of the first aggregate is less than the particle size of the second aggregate, less than the particle size of the third aggregate, and less than the particle size of the fourth aggregate.

[0035] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0036] In terms of weight, the preparation material of the road base composite material provided by the present invention includes 100 parts of aggregate. In the present invention, the aggregate includes the following components in weight: lithium slag, first aggregate, 15 to 30 parts of second aggregate, 20 to 40 parts of third aggregate and 20 to 30 parts of fourth aggregate; the total weight of the lithium slag and the first aggregate is 5 to 35 parts, and the weight of the lithium slag is not 0.

[0037] In the present invention, the lithium slag is preferably solid waste generated by the process of producing lithium carbonate from lithium mica through a sulfate process. In the present invention, the lithium slag preferably includes, by weight percentage of oxides: 35-55% SiO2, 15-33% Al2O3, 3-10% K2O, 2-10% Na2O, 3-8% SO3, 0-15% CaO and 0-1.5% Li2O. In the present invention, the lithium slag preferably also includes other inevitable substances. In a specific embodiment of the present invention, by weight percentage of oxides, the lithium slag further preferably includes: 42.3% SiO2, 23.9% Al2O3, 7.2% K2O, 4.79% Na2O, 6.8% SO3, 5.93% CaO and 0.4% Li2O, etc. In the present invention, the particle size of the lithium slag is preferably less than 2.36mm, D 10 Preferably 23.59 μm, D 50 Preferably 162.16 μm, D 90 The preferred surface area is 675.96 μm, and the preferred specific surface area is 40 to 80 m 2 / kg, preferably 59m 2 / kg. In the present invention, the lithium slag preferably also contains harmful substances, and the harmful substances preferably include beryllium, thallium, manganese, fluorine and zinc. In the present invention, the leaching concentration of harmful substances (beryllium, thallium, manganese, fluorine, zinc) in lithium slag is determined by "Solid Waste Leaching Toxicity Leaching Method-Horizontal Oscillation Method" (HJ 557-2010), and the results are: beryllium 0-20μg / L, thallium 0-5μg / L, manganese 0-1.5mg / L, fluorine 0-10mg / L, zinc 0-2mg / L. In the present invention, the lithium slag can replace part of the first aggregate. At the same time, the active ingredients contained in the lithium slag enable it to replace part of the cement, reducing the cost of road base composite materials and indirectly reducing the carbon emissions of cement and aggregate industrial production. In a specific embodiment of the present invention, the 3d, 7d and 28d compressive strength activity indexes of the lithium slag measured according to "Pozzolanic Mixtures for Cement" (GB T 2847-2022) are preferably 62%, 65% and 67%, respectively.

[0038] In the present invention, the materials of the first aggregate, the second aggregate, the third aggregate and the fourth aggregate are preferably limestone or limestone, and more preferably limestone.

[0039] In the present invention, the particle size of the first aggregate is less than the particle size of the second aggregate, less than the particle size of the third aggregate, and less than the particle size of the fourth aggregate.

[0040] In a specific embodiment of the present invention, the particle size of the first aggregate is preferably less than 5 mm; the particle size of the second aggregate is preferably greater than or equal to 5 mm, and less than 10 mm; the particle size of the third aggregate is preferably greater than or equal to 10 mm, and less than 20 mm, and the particle size of the fourth aggregate is preferably greater than or equal to 20 mm, and less than 30 mm.

[0041] In the present invention, in the aggregate, the total weight of the first aggregate and the lithium slag is preferably 10 to 30 parts, more preferably 15 to 25 parts, and specifically preferably 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts. In the present invention, the weight of the lithium slag preferably accounts for 1 to 100% of the total weight of the lithium slag and the first aggregate, more preferably 20 to 100%, and specifically preferably 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%.

[0042] In the present invention, in the aggregate, the weight proportion of the second aggregate is preferably 20 to 25 parts, and specifically preferably 15 parts, 20 parts, 23 parts, 25 parts, 28 parts or 30 parts.

[0043] In the present invention, in the aggregate, the weight proportion of the third aggregate is preferably 25 to 35 parts, and specifically preferably 20 parts, 25 parts, 28 parts, 30 parts, 35 parts or 40 parts.

[0044] In the present invention, among the aggregates, the weight proportion of the fourth aggregate is preferably 22 to 28 parts, and specifically preferably 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts or 30 parts.

[0045] In parts by weight, the preparation material of the road base composite material provided by the present invention includes 1 to 5 parts of cement, and is preferably 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the cement is preferably PO.42.5 cement. In the present invention, the 3d and 28d compressive strengths of the cement are preferably 29.6MPa and 54.7MPa, respectively, and the 3d and 28d splitting strengths are preferably 5.8MPa and 8.8MPa, respectively. In the present invention, the lithium slag contains calcium oxide, gypsum, active SiO2 and Al2O3 and other components, and the addition of the lithium slag can reduce the amount of cement. In a specific embodiment of the present invention, for every 5 parts by weight of lithium slag added, 0.5 parts by weight of cement can be reduced.

[0046] In the present invention, the active ingredients in the lithium slag can undergo a secondary hydration reaction with the hydration product Ca(OH)2 of cement to generate hydration products such as CSH gel and calcium sulfoxide (AFt), which can seal harmful substances and reduce their release. At the same time, the hydration products fill the gaps between the lithium slag particles through physical sealing, reduce porosity and permeability, and prevent harmful substances from leaking out. The high pH environment provided by the hydration products promotes the conversion of many harmful substances into insoluble compounds, further inhibiting the dissolution of harmful substances. In addition, the active ingredients in the lithium slag are converted into stable minerals through the secondary hydration reaction, reducing the release of harmful substances. In addition, the hydration products can increase the compactness of the road base composite material and seal the microscopic pores of the road base composite material, thereby enhancing the mechanical properties and shrinkage properties of the road base composite material.

[0047] The preparation material of the road base composite material provided by the present invention comprises 4 to 8 parts of water by weight. In the present invention, the water is preferably tap water.

[0048] The present invention also provides a method for preparing the road base composite material described in the above technical solution, comprising the following steps:

[0049] Mixing aggregate, cement and water to obtain a mixture;

[0050] The mixed material is cured to obtain the road base composite material.

[0051] The present invention mixes aggregate, cement and water to obtain a mixture. The present invention does not specifically limit the mixing operation, as long as the materials can be fully mixed.

[0052] After obtaining the mixture, the present invention performs curing on the mixture to obtain the road base composite material.

[0053] In the present invention, the curing parameters include: the ambient humidity is preferably 98%, and the temperature is preferably 20±2°C.

[0054] The present invention also provides the use of the road base composite material described in the above technical solution or the road base composite material prepared by the preparation method described in the above technical solution in road base construction.

[0055] The present invention does not specifically limit the application mode of the road base composite material, and those skilled in the art can configure it according to actual needs.

[0056] The road base composite material provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] The following examples are used in the following raw materials:

[0058] Lithium slag is the solid waste generated by the process of producing lithium carbonate from lithium mica through sulfate process. According to the "Solid Waste Leaching Toxicity Leaching Method-Horizontal Oscillation Method" (HJ 557-2010), the concentration of harmful substances in lithium slag was measured, and the results were: beryllium 2.810μg / L, thallium 1.429μg / L, manganese 0.111mg / L, fluorine 7.681mg / L, zinc 0.025mg / L. In terms of weight percentage of oxides, lithium slag includes 42.3% SiO2, 23.9% Al2O3, 7.2% K2O, 4.79% Na2O, 6.8% SO3, 5.93% CaO and 0.4% Li2O, etc.; the particle size of lithium slag is less than 2.36mm, and the specific surface area is 59m 2 / kg, and the compressive strength activity indexes at 3d, 7d and 28d were 62%, 65% and 67% respectively.

[0059] The particle size of the first aggregate (limestone) is less than 5 mm, the particle size of the second aggregate (limestone) is greater than or equal to 5 mm and less than 10 mm, the particle size of the third aggregate (limestone) is greater than or equal to 10 mm and less than 20 mm, and the particle size of the third aggregate (limestone) is greater than or equal to 20 mm and less than 30 mm.

[0060] The cement is PO.42.5 cement, and the 3d and 28d compressive strengths are 29.6MPa and 54.7MPa respectively, and the 3d and 28d splitting strengths are 5.8MPa and 8.8MPa respectively.

[0061] Example

[0062] The material formulas for preparing the road base composite materials in Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1.

[0063] Table 1 Preparation material ratio of road base composite materials in Examples 1 to 5 and Comparative Examples 1 to 3 (parts by weight)

[0064] Preparation Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Fourth aggregate 24 24 24 24 24 24 24 24 Third Aggregate 28 28 28 28 28 28 28 28 Second aggregate 23 23 23 23 23 23 23 23 First Aggregate 20 15 10 5 0 25 25 25 Lithium slag 5 10 15 20 25 0 0 0 cement 3.5 3.0 2.5 2.0 1.5 4.0 3.5 3.0 water 5.15 5.86 6.45 7.33 7.81 4.45 4.37 4.31

[0065] The prepared materials were mixed according to the formula in Table 1, and road base composite material samples were prepared and cured according to the Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG 3441-2024).

[0066] The leaching concentrations of harmful substances (beryllium, thallium, manganese, fluorine, and zinc) in the road base composite material before maintenance and after 7 days, 28 days, and 90 days of maintenance were determined using the "Solid Waste Leaching Toxicity Leaching Method-Horizontal Oscillation Method" (HJ 557-2010). The results are shown in Tables 2 and 3.

[0067] Table 2 Leaching concentration and regulatory limits of harmful substances in road base composite materials before maintenance in Examples 1 to 5

[0068]

[0069]

[0070] It can be seen from Table 2 that the application of lithium slag in road base composite materials can effectively solidify harmful substances in lithium slag. The leaching concentrations of beryllium, thallium, manganese, fluorine and zinc in lithium slag raw materials are 2.810μg / L, 1.429μg / L, 0.111mg / L, 7.681mg / L and 0.025mg / L respectively. In Example 1, the leaching concentration of each toxic substance decreased by 99.1%, 97.1%, 98.2%, 95.8%, and 88.0%, respectively; in Example 2, the leaching concentration of each toxic substance decreased by 99.0%, 96.0%, 98.2%, 95.3%, and 80.0%, respectively; in Example 3, the leaching concentration of each toxic substance decreased by 98.8%, 92.4%, 97.3%, 94.8%, and 80.0%, respectively; in Example 4, the leaching concentration of each toxic substance decreased by 86.5%, 80.3%, 96.4%, 94.0%, and 76.0%, respectively; in Example 5, the leaching concentration of each toxic substance decreased by 98.5%, 55.6%, 95.5%, 93.1%, and 72.0%, respectively. Therefore, the application of lithium slag in road base composite materials can effectively solidify the harmful substances in lithium slag, and its leaching concentration is far lower than the limits specified in GB 18599-2020 and GB 8978-1996 in my country, thus realizing the safe application of lithium slag.

[0071] Table 3 Harmful substance leaching concentration of the road base composite material obtained in Example 5 at different curing ages

[0072] element Example 5 (7d) Example 5 (28d) Example 5 (90d) Beryllium (μg / L) 0.043 0.031 0.026 Thallium (μg / L) 0.635 0.109 0.038 Manganese (mg / L) 0.005 0.004 0.004 Fluoride (mg / L) 0.532 0.073 0.048 Zinc (mg / L) 0.007 0.005 0.005

[0073] As shown in Table 3, the leaching concentration of harmful substances in the road base composite material increases with the increase of curing time. Compared with the road base composite material with a curing age of 7 days, the road base composite material with a curing age of 28 days can reduce the leaching concentration of beryllium, thallium, manganese, fluorine, and zinc by about 27.9%, 82.8%, 20.0%, 86.3%, and 28.6%. After further curing to 90 days, the leaching concentrations of beryllium, thallium, manganese, fluorine, and zinc in the road base composite material can be reduced by about 39.5%, 94.0%, 20.0%, 91.0%, and 28.6% compared with the curing age of 7 days. Therefore, applying lithium slag to the base composite material and increasing the curing age can further reduce the curing effect of harmful substances in lithium slag.

[0074] The compressive strength and splitting strength of the road base composite materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 at a curing age of 7 days, the residual compressive strength ratio after a curing age of 90 days and 10 freeze-thaw cycles, and the shrinkage coefficient at a curing age of 18 days were measured by the JTG 3441-2024 method. The results are shown in Tables 4 and 5.

[0075] Table 4 Road performance indicators of the road base composite materials obtained in Examples 1 to 5

[0076] Performance Indicators Example 1 Example 2 Example 3 Example 4 Example 5 Compressive strength(MPa) 6.5 6.7 5.5 4.6 3.5 Splitting strength(MPa) 0.72 0.75 0.67 0.58 0.46 Freeze-thaw compressive strength ratio (%) 87.1 78.8 78.6 73.0 52.2 Shrinkage coefficient (με / %) 55.63 47.54 51.07 59.14 62.02

[0077] Table 5 Road performance indexes of road base composite materials obtained in comparative examples 1 to 3

[0078] Performance Indicators Comparative Example 1 Comparative Example 2 Comparative Example 3 Compressive strength(MPa) 6.2 4.7 3.8 Splitting strength(MPa) 0.70 0.62 0.55 Freeze-thaw compressive strength ratio (%) 70.5 66.3 61.1 Shrinkage coefficient (με / %) 71.76 69.58 66.32

[0079] It can be seen from Table 4 and Table 5 that under the same cement content, the comparative example 1 and comparative example 2 show that by using 5 parts by weight of lithium slag to replace 5 parts by weight of the first aggregate, the compressive strength, splitting strength, frost resistance and shrinkage performance of the obtained road base composite material are respectively improved by 38.3%, 16.1%, 31.4% and 20.0%. The comparative example 2 and comparative example 3 show that by using 10 parts by weight of lithium slag to replace 10 parts by weight of the first aggregate, the compressive strength, splitting strength, frost resistance and shrinkage performance of the obtained road base composite material are respectively improved by 76.3%, 36.4%, 29.0% and 28.3%. In addition, by comparing the comparative example 1 and comparative example 1, that is, by using 5 parts by weight of lithium slag to replace 5 parts by weight of the first aggregate and 0.5 parts by weight of cement, the compressive strength, splitting strength, frost resistance and shrinkage performance of the obtained road base composite material are respectively improved by 4.8%, 2.9%, 23.5% and 22.5%. Comparing Example 2 with Comparative Example 1, that is, using 10 parts by weight of lithium slag to replace 10 parts by weight of the first aggregate and 1 part by weight of cement, the compressive strength, splitting strength, antifreeze performance and shrinkage performance of the obtained road base composite material are respectively improved by 8.1%, 7.1%, 11.8% and 33.8%. Comparing Example 5 with Comparative Example 3, it can be seen that using 25 parts by weight of lithium slag to replace 25 parts by weight of the first aggregate and 1.5 parts by weight of cement, the mechanical properties, antifreeze performance and shrinkage performance of the obtained road base composite material are equivalent, and it can be used for the base of expressways and first-class highways for medium and light traffic, and the base of second-class highways and below for first-class heavy traffic.

[0080] As can be seen from the above analysis, the use of unactivated lithium slag to replace the non-renewable first aggregate (fine aggregate) and cement can not only effectively solidify harmful substances such as beryllium, thallium, manganese, fluorine, zinc in the lithium slag, but also effectively increase the compressive strength, splitting strength, frost resistance and shrinkage performance of the road base composite material. Therefore, the road base composite material proposed by the present invention can not only achieve efficient disposal of lithium slag solid waste and solidification of harmful substances under the condition of not using alkali activator, mechanical grinding and high temperature calcination activated lithium slag, but also save the amount of cement and non-renewable fine aggregate, and effectively improve the compressive strength, splitting strength, frost resistance and shrinkage performance of the road base composite material. The road base composite material of the present invention provides a new research idea for the efficient recycling of lithium slag solid waste and the low-carbon sustainable construction of roads.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A road base composite material, characterized in that: The preparation comprises the following parts by weight: 100 parts of aggregate, 1-5 parts of cement, 4-8 parts of water; The aggregate comprises the following components in parts by weight: Lithium slag, first aggregate, 15-30 parts of second aggregate, 20-40 parts of third aggregate and 20-30 parts of fourth aggregate; The total weight of the lithium slag and the first aggregate is 5 to 35 parts, and the weight of the lithium slag is not 0; The particle size of the first aggregate is less than the particle size of the second aggregate, less than the particle size of the third aggregate, and less than the particle size of the fourth aggregate.

2. The road base composite material according to claim 1, characterized in that: The weight of the lithium slag accounts for 1-100% of the total weight of the lithium slag and the first aggregate.

3. The road base composite material according to claim 1, characterized in that: Calculated in terms of weight percentage of oxides, the lithium slag comprises: 35-55% SiO2, 15-33% Al2O3, 3-10% K2O, 2-10% Na2O, 3-8% SO3, 0-15% CaO and 0-1.5% Li2O.

4. The road base composite material according to claim 1, characterized in that: The particle size of the lithium slag is less than 2.36 mm.

5. The road base composite material according to claim 1, characterized in that: The first aggregate, the second aggregate, the third aggregate and the fourth aggregate are all made of limestone or limestone.

6. The road base composite material according to claim 1 or 5, characterized in that: The particle size of the first aggregate is less than 5 mm, the particle size of the second aggregate is greater than or equal to 5 mm and less than 10 mm, the particle size of the third aggregate is greater than or equal to 10 mm and less than 20 mm, and the particle size of the fourth aggregate is greater than or equal to 20 mm and less than 30 mm.

7. The road base composite material according to claim 1, characterized in that: The cement is PO.42.5 cement.

8. The method for preparing the composite material for road base according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing aggregate, cement and water to obtain a mixture; The mixed material is cured to obtain the road base composite material.

9. The preparation method according to claim 8, characterized in that: The curing parameters include: ambient humidity of 98% and temperature of 20±2°C.

10. Use of the road base composite material according to any one of claims 1 to 7 or the road base composite material prepared by the preparation method according to any one of claims 8 to 9 in road base construction.